BASIC EDUCATION AS THE FOUNDATION FOR NATIONAL DEVELOPMENT: PREPARING QUALITY HUMAN RESOURCES WITH CHARACTER FOR THE FUTURE OF THE COUNTRY; LITERATURE REVIEW METHOD - Rudianto Rudianto; Rosijanih Arbie (International Journal of Teaching and Learning, 2025)
Basic education is the main foundation in preparing quality human resources that will determine the sustainability of national development. At this level, children are not only equipped with basic skills such as reading, writing, and arithmetic, but also instilled with moral, social, and national values as the basis for character building. This study uses a literature review method by examining various references in the form of books, scientific journals, and relevant policy documents to analyse the role of basic education in preparing quality human resources with character. The results of the study show that basic education contributes greatly to improving literacy, numeracy, emotional intelligence, and social skills, which are important indicators of human resource quality. On the other hand, basic education also serves to build national character by instilling the values of discipline, responsibility, mutual cooperation, tolerance, and integrity, which are essential for maintaining national unity. Therefore, strengthening basic education in terms of access, curriculum, teaching staff, and learning environment is a strategic investment to realise the vision of Indonesia Emas 2045 with a generation that is competent, has noble character, and is globally competitive.